Perilaku Pemustaka Dalam Temu Kembali Koleksi Dengan Menggunakan OPAC Berbasis SLIMS - Mujiati Mujiati (Pustakaloka, 2014)
Abstract: An  increase of  library collection and  information explosion causes  problems  on    information  retrieval  for  library  users.  Those explosion will be helpful for users using Online Public Access Catalog (OPAC). This article tries to explore the use of OPAC based SLIMs on STAIN Ponorogo  library. OPAC proves  to help users  on  retrieval  be easier and faster, beside its obstacles